2010
DOI: 10.1097/fjc.0b013e3181bfb1a2
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects With Equivalent Low-density Lipoprotein Cholesterol Reduction: Comparative Study Between Simvastatin and Simvastatin/Ezetimibe Coadministration

Abstract: The 2 forms of treatment presented similar pleiotropic effects: improvement in endothelial function and decrease in hs-CRP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…These results are in agreement with recent studies showing that co-administration of ezetimibe with statins provides an additional improvement in serum LDL-C and overall lipid profile in patients with inadequate lipid control while on statin monotherapy [1419]. Furthermore, recent reports indicate that ezetimibe exerts pleiotropic effects on cardiovascular function which are similar [26] or improved [27, 28] compared to statin monotherapy, while additional trials are ongoing which will further analyze the impact of ezetimibe on these effects [29, 30]. …”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with recent studies showing that co-administration of ezetimibe with statins provides an additional improvement in serum LDL-C and overall lipid profile in patients with inadequate lipid control while on statin monotherapy [1419]. Furthermore, recent reports indicate that ezetimibe exerts pleiotropic effects on cardiovascular function which are similar [26] or improved [27, 28] compared to statin monotherapy, while additional trials are ongoing which will further analyze the impact of ezetimibe on these effects [29, 30]. …”
Section: Discussionsupporting
confidence: 91%
“…Results were found to be inconstant: six studies found no difference in endothelial function (89,91,94,(96)(97)(98), four found statin alone be better (77,(92)(93)(94), and one study found a beneficial effect of combination therapy over statin alone (90). However, in many of these studies comparing statins vs combination therapy, markedly different lipid lowering effects were found, thus making comparisons difficult (77,(89)(90)(91)94). Two cross-over studies with a reduced risk of confounding and bias, reached discordant conclusions, one showing an improved endothelial function on statin alone (93), and the other not observing any significant difference between the two treatments (97).…”
Section: Ezetimibementioning
confidence: 96%
“…A number of studies have investigated statin therapy versus statins in combination with ezetimibe on endothelial function as a measure of vascular inflammation (77,(89)(90)(91)(92)(93)(94)(95)(96). Results were found to be inconstant: six studies found no difference in endothelial function (89,91,94,(96)(97)(98), four found statin alone be better (77,(92)(93)(94), and one study found a beneficial effect of combination therapy over statin alone (90). However, in many of these studies comparing statins vs combination therapy, markedly different lipid lowering effects were found, thus making comparisons difficult (77,(89)(90)(91)94).…”
Section: Ezetimibementioning
confidence: 99%
“…Между группами показатели в конце курса не различались. О положи-тельном влиянии комбинации Э + C на функцию эндотелия со-общали и другие исследователи [32,48,49].…”
Section: терапевтический архив 12 2014unclassified